CITIZEN PARTICIPATION IN THE DEVELOPMENT OF PUBLIC POLICIES IN VESZPRÉM COUNTY AND THE BALATON REGION - Czuppon, Viktória Csizmadiáné; Galetin, Milena; Muhi, Bela (Poslovna ekonomija, 2021)
The participation of citizens in decision-making process at the local level is a prerequisite for the existence of a democratic society. The importance of local producers’ involvement in this process is important because they contribute to the development of the local community and improve its living conditions. The authors deal with the questions how the local producers in the Veszprém County and the Balaton Region are familiar with these rights, in what extent they use them and what are the obstacles for citizen participation in public life at the local level. In order to examine the whole problem, the survey also includes the representatives of local authorities. This research consists of three parts. After introduction and legislative review, in the second part the results of the survey are presented. The combination of theoretical analysis and empirical research that is characteristic for social sciences is used. Finally, in the last part, recommendations for the improvement of the participation of local citizens in the creating public policies at the local level in the mentioned region are presented.